Pengaruh Intellectual Capital terhadap Kinerja Keuangan pada PD. BPR Garut - Cecep Hamzah (Fakultas Ekonomi Universitas Garut, 2017)
This study entitled The Effect of Intellectual Capital on Financial Performance at PD. BPR Garut. This study aims to determine the intellectual capital and financial performance of PD. BPR Garut for the period 2012 to 2015. This research uses quantitative methods. The data collection technique used is library research and documentation research. While the data processing technique is performed using simple linear regression analysis. The results showed that Intellectual Capital had a positive effect on Return On Assets (ROA), wherein Intellectual Capital at PD. BPR Garut as a whole from the period 2012 to 2015 has increased and is included in the Top Performance category, meaning that human resources, infrastructure and business relations are very good and adequate. Financial Performance (ROA) of PD. BPR Garut as a whole from the period 2012 to 2015 experienced (fluctuations), namely an increase and decrease and more likely to increase in each quarter, and was classified in the predicate for the health status of Bank Indonesia in the fairly healthy category.